Potentiometric and Thermodynamic Studies of Some Azosulfoxine Derivatives and Their Metal Complexes - El-Bindary, A.A.; El-Sonbati, A.Z.; Diab, M.A.; Barakat, A.M. (Journal of Applied Solution Chemistry and Modeling, 2013)
The proton-ligand dissociation constants of some azosulfoxine derivatives and metal-ligand stability constants of their complexes with the metal ions (Mn2+, Co2+, Ni2+ and Cu2+) have been determined potentiometrically in 0.1 M KCl and 50 % (by volume) DMFâ€“water mixture at (298, 308 and 318) K. The stability constants of the formed complexes increases in the order Mn2+, Co2+, Ni2+ and Cu2+. The effect of temperature was studied and the corresponding thermodynamic parameters (ΔG, ΔH and ΔS) were derived and discussed. The dissociation process is non-spontaneous, endothermic and entropically unfavourable. The formation of the metal complexes has been found to be spontaneous, endothermic and entropically favourable.